2001
DOI: 10.1177/089826430101300201
|View full text |Cite
|
Sign up to set email alerts
|

Age Variations in Personal Agency and Self-Esteem

Abstract: The findings describe how age-correlated personal and social factors contribute to, or statistically conceal, older adults' sense of health control, self-efficacy, and self-esteem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 31 publications
3
28
0
9
Order By: Relevance
“…The self-image of individuals seems to decrease with increasing age, which may be related to physiological, social status or loved ones losses. 23 Also regarding the variable age, according to a study in Ontario, in Canada, older respondents report lower health control, self-efficacy and self-esteem since the greater the survival, the greater the chance of developing chronic diseases 24 . These disorders can limit or restrict the possibilities of social support because of changes in the emotional state by restricting the activities that encourage self-esteem in the "co-residents" elderly.…”
Section: Discussionmentioning
confidence: 99%
“…The self-image of individuals seems to decrease with increasing age, which may be related to physiological, social status or loved ones losses. 23 Also regarding the variable age, according to a study in Ontario, in Canada, older respondents report lower health control, self-efficacy and self-esteem since the greater the survival, the greater the chance of developing chronic diseases 24 . These disorders can limit or restrict the possibilities of social support because of changes in the emotional state by restricting the activities that encourage self-esteem in the "co-residents" elderly.…”
Section: Discussionmentioning
confidence: 99%
“…O envelhecimento é acompanhado por perdas que contribuem para a redução da satisfação com o próprio corpo (Gripo & Hill, 2008), fato que pode estar relacionado às perdas físicas, funcionais e sociais (Schieman & Campbell, 2001). …”
Section: St Meurer Cb Luft Tr Benedetti Gz Mazounclassified
“…Efficacious people are more able to persevere in the face of challenges because they believe they can change situations and behaviours to produce more positive outcomes (Schieman & Campbell, 2001). The concept of self-efficacy was enunciated and refined by Bandura (1977), who observed that people who perceived themselves as powerless to exert influence over situations tended to be overwhelmed by apprehension, apathy, and despair.…”
Section: Age and Self-efficacymentioning
confidence: 99%